Casting light on the dark web a guide for safe exploration - Beckstrom, Matthew (LITA guides., 2019)
"This book is an easy-to-read and comprehensive guide to understanding how the Dark Web works and why you should be using it! Readers are led on a tour from how to download the platform for personal or public use, to how it can best be utilized for finding information. This guide busts myths and informs readers, remaining jargon-free"--